Application of Simulation Technology in Football Training: A Systematic Review of Empirical Studies - Teng Jia; Jirarat Sitthiworachart; John Morris (My University, 2024)
Background This review aimed to cover the characteristics and functions of simulation tools applied to football training, the process and results of empirical research, the benefits of simulation tools for football training, and existing challenges. Materials and Methods To investigate and analyze the effect of simulation technology in football training, the PRISMA method was used to systematically review 18 relevant empirical studies published between January, 2014 and July, 2023. Results The study identified three types of tools for applying simulation technology to football training, including head-mounted displays, Cave Automatic Virtual Environment (CAVE), and Screen-Based Simulation. These tools have been effective in training football playing techniques (including goalkeeping, heading, etc .) as well as football tactical skills (including perception-cognitive and decision-making) and can be used as a supplement to regular training. Conclusion If simulation technology is to enhance football training, we suggest that it is necessary to carefully verify the validity of the tool and the long-term impact of simulation training on participants and verify that simulation actually translates to real-world games. At the same time, it is suggested that future research could explore training with mixed VR and AR to develop more realistic and effective training platforms.
Keywords: Sport Psychology and Performance